2021
DOI: 10.3389/fpls.2021.642199
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Biomass Quantity and Quality by Improved Mixotrophic Culture of the Diatom Phaeodactylum tricornutum

Abstract: Diatoms are photoautotrophic unicellular algae and are among the most abundant, adaptable, and diverse marine phytoplankton. They are extremely interesting not only for their ecological role but also as potential feedstocks for sustainable biofuels and high-value commodities such as omega fatty acids, because of their capacity to accumulate lipids. However, the cultivation of microalgae on an industrial scale requires higher cell densities and lipid accumulation than those found in nature to make the process e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 89 publications
5
6
0
Order By: Relevance
“…Ng was grown in 1L photobioreactors under four different conditions, namely phototrophy, mixotrophy, and bubbled either only with air (PHOTO_AIR and MIXO_AIR) or with CO 2 -rich air (PHOTO_CO 2 and MIXO_CO 2 ). We found that the mixotrophic growth of Ng in the presence of both organic and inorganic carbon (MIXO_CO 2 ) was the best condition for increasing its industrial potential, as recently shown for the diatom Phaeodactylum tricornutum [27]. However, our results showed similar biomass productivity for Ng grown regardless of the presence of organic, inorganic, or both carbon sources; in contrast, a significant increase of biomass for Phaeodactylum tricornutum was found only in the presence of both carbon sources.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Ng was grown in 1L photobioreactors under four different conditions, namely phototrophy, mixotrophy, and bubbled either only with air (PHOTO_AIR and MIXO_AIR) or with CO 2 -rich air (PHOTO_CO 2 and MIXO_CO 2 ). We found that the mixotrophic growth of Ng in the presence of both organic and inorganic carbon (MIXO_CO 2 ) was the best condition for increasing its industrial potential, as recently shown for the diatom Phaeodactylum tricornutum [27]. However, our results showed similar biomass productivity for Ng grown regardless of the presence of organic, inorganic, or both carbon sources; in contrast, a significant increase of biomass for Phaeodactylum tricornutum was found only in the presence of both carbon sources.…”
Section: Discussionsupporting
confidence: 85%
“…Ng was grown in 1L photobioreactors under four different conditions, namely phototrophy, mixotrophy, and bubbled either only with air (PHOTO_AIR and MIXO_AIR) or with CO2-rich air (PHOTO_CO2 and MIXO_CO2). We found that the mixotrophic growth of Ng in the presence of both organic and inorganic carbon (MIXO_CO2) was the best condition for increasing its industrial potential, as recently shown for the diatom Phaeodactylum tricornutum [27]. However, our Figure 8.…”
Section: Discussionsupporting
confidence: 75%
“…Further, in the presence of glycerol, the consumption rate of nutrients increased, as observed for NaNO 3 (M1 -18.86 mg L −1 day −1 , M2 -10.33 mg L −1 day −1 ), whereas in a medium containing urea, nutrient uptake rates were 12 mg L −1 day −1 (M2), 13 mg L −1 day −1 (M3, M4), resulting in the exhaustion of NaNO 3 by 4th day (M1) and urea by 2nd day (M2, M3). The mixotrophic mode of P. tricornutum enhanced the nutrient uptake rate as reported by Villanova et al [52] It can be observed that the nutrient uptake rate in P2 and M2 for NaNO 3 is 5.52 and 10.33 mg L −1 day −1 , respectively, whereas for urea in P2 and M2 it is 10.75 and 12 mg L −1 day −1 , respectively. Interestingly, urea is completely consumed in the medium by the 4th day (in P2, P3, M2, M3), whereas NaNO 3 is exhausted by the 6th day of cultivation (in P1) (Supplementary Information Figures S2, S3).…”
Section: Biomass Production Of P Tricornutumsupporting
confidence: 75%
“…Previous reports have shown the effect of mixotrophy on the growth of P. tricornutum which correlates with our results. [ 21,22,51,52 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation